2008
DOI: 10.1016/j.ijsu.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Tension-free repair versus Bassini technique for strangulated inguinal hernia: A controlled randomized study

Abstract: The use of Lichtenstein "tension-free" technique in emergency treatment of strangulated inguinal hernia is safe, effective with an acceptably low rate of postoperative complications and without recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 14 publications
2
50
0
8
Order By: Relevance
“…In low risk patients, tension-free mesh repair is a safe procedure [44,45]. This technique is not associated with mesh-related complications, such as infections or increased recurrence rates compared to the use in elective setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In low risk patients, tension-free mesh repair is a safe procedure [44,45]. This technique is not associated with mesh-related complications, such as infections or increased recurrence rates compared to the use in elective setting.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a prosthetic mesh in emergency repair is presumed to lead to mesh-related complications such as an increased risk of infection [44,45]. Recent studies have shown that the use of a tension-free mesh in emergency groin hernia repair is not associated with higher morbidity rates.…”
Section: Risk Of Incarceration and Strangulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies could show that an incarcerated groin hernia is not an absolute contraindication for the implantation of non-absorbable meshes, as the complications rates (and especially the infection rates) were similar to those after repair without the use of prosthetic material [2,3].…”
mentioning
confidence: 99%
“…In another study, diVerences were found in the recurrence rates but not in the infection rates. However, patients with inXamed hernia or preoperative peritonitis were excluded from randomization (both of them are present in inXamed Amyand's hernia) [3].…”
mentioning
confidence: 99%